Periodontal abscess in the anterior mandible due to anterior crossbite mistaken for sports trauma: Periodontal abscess in the anterior mandible due to anterior crossbite mistaken for sports trauma - T, Iki Nopalia Syam; Zahbia, Zia Nurul; Syahrir, Syakriani (Makassar Dental Journal PDGI Makassar, 2025)
Anterior crossbite can cause pathological conditions in the periodontal tissues, such as tooth mobility similar to dentoalveolar post-traumatic conditions. An 8-year-old boy presented with complaints of mobility in the mandibular anterior teeth. Dental trauma treatment using splints worsened the patient's condition. Through communication and pedodontic triangle principle, it was diag-nosed as periodontal abscess due to anterior crossbite. Treatment was carried out using a bite elevation on the posterior teeth as it did not increase the occlusal pressure load received on the mandibular anterior teeth. The crossbite was corrected and the periodontal status improved within 7 days. It was concluded that diagnosis in children is challenging due to frequent misdiag-nosis. Treatment of periodontal abscess due to anterior crossbite using bite elevation on posterior teeth as it is considered as an emergency treatment to reduce occlusal pressure on mandibular anterior teeth.